(untitled) (Revista Cocar, 2023)
Este artigo analisa a educação e o trabalho de meninas na cidade de Belém do Pará, durante a Primeira República. Para tanto, utilizou-se alguns dados das seguintes fontes judiciais: processos criminais de “menores”, no período de 1890 a 1905 catalogados no Centro de Memória da Amazônia – CMA; documentos da chefatura de polícia e livros de ocorrências da Cadeia Pública de São José, no período de 1886 a 1911, catalogados no Arquivo Público do Estado do Pará – APEP. Descreve-se a constituição da infância e o modelo de educação proposto para meninas pobres da capital paraense e sua relação com a prostituição; e o imaginário social na perspectiva histórico-crítica dos discursos jurídicos contidos nestes registros, de acordo com o código penal de 1890. Este estudo demonstra um viés da realidade socioeducacional e cultural brasileira de “menores” judicialmente condenados, no período republicano. Palavras-chave: Imaginário Social; Discursos; Fontes Judiciais; História da Educação no Pará. Abstract: The goal of this article is to analyze the education and work of young girls in the city of Belém do Pará during the period of the first republic. In order to do this, data of the following judicial sources have been gathered: criminal processes of minors from the period of 1890 through 1905 that were cataloged in the memory center of Amazonia - CMA; documents from the police office and log books from the public prison of São José during the period of 1886 to 1911. Those documents were cataloged in the public archives of the state of Pará - APEP. This article describes the constitution of the childhood and the educational model proposed to poor girls of the capital as well as its connection with prostitution. It also describes the social imaginary considering the historical-political perspective of the legal arguments in those registries, in accordance with the criminal code of 1890. This study demonstrates one side of the Brazilian socio educational and cultural reality of judicially convicted minors during the period of the first republic. Keywords: Social Imaginary; Arguments; Judicial Sources; History of Education in Pará.